Optimalisasi Kepuasan Kerja melalui Pengelolaan Beban Kerja, Work Family Conflict, dan Social Support pada Pegawai Sekretariat DPRD Kota Surakarta - Fii Ahsani, Riska; Cheren Adina Putri; Wikan Budi Utami (ITB AAS Indonesia Surakarta, 2025)
Job satisfaction is an attitude or emotional feeling felt by employees and how they view their work, whether it is a pleasant or unpleasant feeling that can be reflected from how someone does their job. The existence of employees in carrying out their duties and obligations cannot be separated from the influence of internal factors and external factors that lead to changes in employee job satisfaction. In order to improve employee job satisfaction, we need to know the factors that influence it. The purpose of this study is to analyze workload, work family conflict and social support on employee job satisfaction. This study is a survey of employees of the Surakarta City Regional House of Representatives Secretariat. The type of data used is quantitative data. The data source used is primary. The population in this study were employees of the Surakarta City Regional House of Representatives Secretariat. The number of samples used in this study was 58 employees. The sampling technique used the census technique. Data analysis used multiple linear regression tests, t tests, F tests and determination coefficient tests. The results showed that workload had a significant effect on employee job satisfaction, work family conflict had a significant effect on employee job satisfaction, social support had a significant effect on employee job satisfaction. The results showed that the coefficient was 0.783. This means that the contribution of the influence of the independent variables Workload, Work Family Conflict and Social Support to Job Satisfaction is 78.3%.